Describing The Inclusivity of Elementary School Buildings for Pupils with Disabilities - Rwehn Izeah Ricaplaza; Ma Antonette G Salumag; Francis May S Valmorida; Alfer Jann D Tantog (Research Synergy Foundation, 2025)
This research examines the inclusivity and accessibility of the Columban Elementary School and College Department building in Pagadian City, with a focus on key features such as parking areas, entrances, doors, corridors, toilets, and stairways. A survey, adapted from the Batas Pambansa Bilang 344 compliance checklist, was administered to 42 Bachelor of Elementary Education (BEED) students and 53 Grade 6 pupils. Quantitative data analysis was employed to interpret the responses. The results indicate that both Grade 6 pupils and BEED students generally perceive the school buildings as accessible, with Grade 6 pupils rating accessibility features slightly higher. A statistical test revealed a significant difference between the perceptions of Grade 6 pupils and BEED students, suggesting that younger students may have a more favorable view of the school's accessibility. These findings highlight the need for ongoing assessment of school infrastructure to ensure it meets the needs of all students, especially those with disabilities. The study proposes an action plan to improve accessibility, including feedback mechanisms, staff training on inclusive practices, collaboration with accessibility experts, and regular audits. By emphasizing the importance of an inclusive school environment, this research aims to contribute to the development of educational settings that support all learners, including those with disabilities.